Experimental and simulation-based investigation of serrated chip formation in high-speed milling of Inconel 718 - Mustafa, Ghulam; Li, Binxun; Zhang, Song (International journal of advanced manufacturing technology, 2025)
Ni-based superalloys, especially Inconel 718, present significant challenges when it comes to high-speed milling due to their distinctive properties such as low thermal conductivity and high-temperature strength. Thermomechanical effects are attributable to synergistic coupling between thermal and mechanical processes that occur during machining and have a considerable impact on chip formation. Unlike the turning operation, the milling process contains a variety of both rotational and translational movements, along with the creation of rough and irregular undeformed chip thickness. Therefore, it is crucial to examine the thermomechanical impacts on the mechanism of serrated chip development. To comprehend serrated chip development during high-speed milling of Inconel 718 alloy, this research explores a numerical methodology to understand serrated chip generation in high-speed milling of Inconel 718 and incorporates the collective effect of material constitutive behavior with an energy-based ductile failure mechanism. Initially, a simulation model for high-speed milling was proposed by integrating the Johnson–Cook damage criterion with the viscoplastic constitutive material model to account for shear localization. Subsequently, the experimental data were used to validate the proposed finite element (FE) model. TiAlN-coated insert owing to its high oxidation resistance and AlTiN-coated milling insert due to its high temperature stability were employed for the milling experiments. The numerical findings, in particular for the chip contour and cutting forces, are in correspondence with the experimentally described outcomes to examine the thermomechanical effects inducing chip formation. In contrast to the TiAlN-coated insert, the AlTiN-coated insert comprises higher cutting forces and temperature. FE analysis provides a thorough explanation of the physical mechanism subject to the formation of serrated segments and micro-cracks. This research provides a brief knowledge of serrated chip development during high-speed milling of Inconel 718, advancing the process parameters and attaining the required level of surface integrity in the milled workpiece, which could lead to improved operational cost as well as improved accuracy in various industries including aerospace and energy sectors, where Inconel 718 is commonly used.